2010
DOI: 10.1038/cr.2010.25
|View full text |Cite
|
Sign up to set email alerts
|

Length of the ORF, position of the first AUG and the Kozak motif are important factors in potential dual-coding transcripts

Abstract: A single mammalian transcript normally encodes one protein, but the transcript of GNAS (G-protein α-subunit) contains two reading frames and produces two structurally unrelated proteins, XLαs and ALEX. No other confirmed GNAS-like dual-coding transcripts have been reported to date, even though many such candidate genes have been predicted by bioinformatics analysis. In this study, we constructed a series of vectors to test how two protein products were translated from a single transcript in vitro. The length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…For each configuration, the combinations of strong and/or weak Kozak motifs [6] were respectively introduced to flank the two AUG codons. Thus, Xu et al [5] were able to systematically examine the impact of three key factors on the translational activity of a two-ORF-containing transcript: the position of the start codon, the ORF length and the strength of the Kozak motif. Using fluorescence imaging techniques and western blots, they detected dual protein products in four out of the eight transcript subtypes under survey.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…For each configuration, the combinations of strong and/or weak Kozak motifs [6] were respectively introduced to flank the two AUG codons. Thus, Xu et al [5] were able to systematically examine the impact of three key factors on the translational activity of a two-ORF-containing transcript: the position of the start codon, the ORF length and the strength of the Kozak motif. Using fluorescence imaging techniques and western blots, they detected dual protein products in four out of the eight transcript subtypes under survey.…”
mentioning
confidence: 99%
“…Using the rules inferred from their experimental studies, Xu et al [5] further performed a bioinformatic analysis to screen the dual-coding transcripts in the human and mouse genomes. They found that about 170 human transcripts are potentially dual coding and only 18 are conserved in the mouse genome.…”
mentioning
confidence: 99%
See 3 more Smart Citations